(untitled) (Pravaha, 2023)
The advent of ChatGPT and other AI tools represents a transformative shift in various domains, notably in education and education. This paper explores how AI-driven conversational models are redefining traditional practices, offering personalized learning experiences, and enhancing accessibility to knowledge. Chat GPT has amassed over a million users in just five days since its launch, making it a significant participant in the Internet and technology sectors. ChatGPT, as an exemplar of generative AI, provides on-demand assistance, fosters interactive learning environments, and supports educators with resource generation and administrative tasks. Beyond education, these tools are revolutionizing fields such as customer service, content creation, and healthcare, driving efficiencies and enabling innovative solutions. This paradigm shift raises important questions about the future role of human expertise, ethical considerations, and the potential for AI to augment rather than replace human capabilities. By examining the implications and opportunities presented by these technologies, this paper aims to provide a comprehensive overview of how AI tools are reshaping our world and to offer insights into navigating this evolving landscape. This work thoroughly examines the ethical and privacy difficulties that ChatGPT offers, despite its potential.